Legal Analysis of Marine Pollution Due to Oil Spill by MV Ever Judger Ship in Balikpapan Bay: Review of the Implementation of the Strict Liability Principle in Law No. 32 of 2009 - Ahmad Salman Aman (Law Research Review Quarterly, 2025)
The oil spill by the MV Ever Judger in Balikpapan Bay in 2018 is one of the marine pollution cases that has received widespread attention in Indonesia. This incident caused significant environmental damage and caused social, economic and ecological losses. This article aims to analyze the application of the strict liability principle in Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH) in the context of the case. The principle of strict liability allows the liability of the perpetrator of pollution without having to prove the element of fault. Through a normative juridical approach, this article dissects the legal basis of marine pollution liability and assesses the effectiveness of its application to polluters from the shipping sector. The results of the discussion show that although the principle of strict liability is accommodated in Indonesian environmental law, its application still faces challenges in practice, especially in terms of law enforcement and proof of ecological losses.